HUBUNGAN ASUPAN GIZI DAN TINGGI BADAN IBU DENGAN STATUS GIZI ANAK BALITA - Hanum, Farida; Khomsan, Ali; Heryatno, Yayat (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2014)
The objectives of this study were to analyze relationship of maternal height, nutrients intake and nutritional status in children under five years. The study design used was cross-sectional study with 90 children as subjects that consisted of 47 stunting children and 43 normal children. This study showed that short mothers (height <150 cm) were more prevalent in stunting children (74.5%) compared to normal children (60.5%). Energy and protein adequacy level of stunting and normal children were relatively severe deficient. There were no significant relationship between maternal height and energy adequacy level with nutritional status. However, there was a negative relationship between protein adequacy level with nutritional status (p<0.05; r=-0.223).